Blind document image quality prediction based on modification of quality aware clustering method integrating a patch selection strategy. (15th October 2018) - Alaei, Alireza; Conte, Donatello; Martineau, Maxime; Raveaux, Romain
Highlights: A blind image quality assessment measure based on foreground information is proposed. The proposed measure is based on a Bag-of-Visual-Words and patch selection strategy. The proposed measure is particularly adapted for document images. The proposed measure is competitive with the state-of-the-art methods. The proposed method is suitable for expert systems embedded in mobile applications. Abstract: The quality of document images has direct impacts on the performance of document image processing systems. Document Image Quality Assessment (DIQA) is, therefore, of fundamental importance to a numerous document processing applications. As manual quality assessment is almost impossible for a huge volume of document images generated in day-to-day life, it is critical to develop intelligent machine operated methods to estimate the quality of document images. In this paper, a blind document image quality assessment method is proposed to deal with the problem of DIQA in real scenarios, as reference images are not always available. To estimate the quality of a document image, the document is first sampled into a set of patches. The extracted patches are then filtered out based on their level of foreground information using a patch selection strategy. For every selected patch, a cluster assignment is then performed to obtain its quality from a quality aware bag of visual words constructed using k-means clustering. An average pooling is finally employed to estimate the quality of the input document image. To evaluate the proposed method, a dataset composed of document images and three scene image datasets were considered for experimentation. The results obtained from the proposed method demonstrate the effectiveness of the proposed DIQA method. These achievements in applied computational intelligence, expert and decision support systems make a good foundation for creating practical tools to automate document image forgery detection, and archiving process.